The Consistent Effectiveness and Safety of Macitentan Therapies Across Idiopathic and Congenital Heart Disease-Associated Pulmonary Arterial Hypertension: A Single-Center Experience - Kaymaz, Cihangir; Tanyeri, Seda; Tokgoz, Hacer Ceren; Akbal, Ozgur Yasar; Karagoz, Ali; Keskin, Berhan; Ozdemir, Nihal (Aves, 2022)
Background: In this single-center study, we evaluated efficacy and safety issues and predictors of survival in patients with idiopathic and congenital heart disease-associated pulmonary arterial hypertension who were under macitentan therapies. Method: Our study retrospectively evaluated 221 patients with pulmonary arterial hypertension enrolled in our single-center study, and mono, dual, and triple macitentan therapies were noted in 30, 115, and 76 patients, respectively. The longitudinal changes in clinical, neurohumoral, and echocardiographic measures of pulmonary arterial hypertension were evaluated. The Registry to Evaluate Early and Long-Term Pulmonary Arterial Hypertension Disease Management, Registryto Evaluate Early and Long-Term Pulmonary Arterial Hypertension Disease Management 2.0, and Registry to Evaluate Early and Long-Term Pulmonary Arterial Hypertension Disease Management Lite 2 scores at baseline, Swedish PAH Registry, Comparative Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension registry, and French Pulmonary Hypertension Network registry risk status both at baseline and first control were assessed. Result: The median follow-up period was 1068 [415-2245] days. Macitentan was associated with significant improvements in functional class, 6-minute walk distance, N-terminal pro-brain natriuretic peptide NT- proBNP), and echocardiographic measures without any deterioration of hemoglobin or hepatic enzymes. The low-risk scores with each model at baseline and/or first control are related to significantly better survival. Age, gender, and log-NT-proBNP in time-fixed and idiopathic pulmonary arterial hypertension, and log-NT-proBNP in time-dependent Cox proportional hazard regression analyses were independent predictors of mortality. Conclusion: Mono- or sequential combination macitentan therapies were associated with sustained benefits in functional class, 6-minute walk distance, NT-proBNP, and echocardiographic measures in patients with idiopathic pulmonary arterial hypertension and congenital heart disease-associated pulmonary arterial hypertension, and low-risk scores at baseline and/or first controls can be translated to better survival.
Keywords: Macitentan; pulmonary arterial hypertension; Eisenmenger syndrome; REVEAL-Lite 2; COMPERA; SPAHR